Epidemiology of New Delhi Enterobacterales in Tuscany during the COVID- 19 pandemic. (20th October 2021) - Porretta, AD; Forni, S; Tavoschi, L; Righi, L; Gemmi, F
Abstract:  : In Tuscany, Italy, colonisation or infection by New Delhi metallo- beta-lactamase-producing carbapenem-resistant Enterobacterales (NDM-CRE) in hospitalised patients has increasingly been observed since 2018, leading in 2019 to the introduction of enhanced control measures successfully reducing transmission. We describe here the impact of the COVID epidemic on the underlying NDM-CRE prolonged outbreak in Tuscany. Data on patients colonised or infected by NDM-CRE reported by Tuscan laboratory surveillance among hospitalised patients in four Tuscan hospitals were collected from 07/2019 to 10/2020. Since February 2020 COVID-19 diagnosis was recorded. Monthly rates of NDM-CRE cases on hospital days in medical and critical care wards were calculated. In March-October 2020 NDM-CRE rates were calculated and stratified by COVID-19 diagnosis. The number of NDM-CRE cases/hospital days in 2019 decreased due to control interventions, however since March 2020 an increase was observed, temporally associated with COVID-19 admissions. In March-October 2020, compared to previous period, NDM-CRE cases had lower median age (73 yrs vs 75), were less likely to have previous hospitalisation episodes (59% vs 75%) and more likely to be admitted to ICU (32% vs 20%). We observed, in the period March-October 2020 a significantly higher rate of NDM-CRE cases per hospital days (256.71/100, 000) in COVID-19 patients, compared to non-COVID-19 ones (452.9/100, 000). Our data suggest a resurgence in NDM-CRE spread among hospitalised patients in Tuscany during COVID pandemic, despite evidence of effective control measures in 2019. Risk of NDM-CRE transmission was significantly higher among COVID patients. Several factors may have contributed to this occurrence, including patients case mix, performance of risk-prone procedures (including antibiotic prescriptions), extended length of stay, availability and usage of personal protective equipment and compliance with infection prevention procedures. Key messages: We observed a relation between admission for COVID-19 and the risk of a hospital acquisition of NDM-CRE. There is the need to conciliate Health Care Associated Infections control measured with COVID-19 protection ones.